Variation in Demography and Life-History Strategies Across the Range of a Declining Mountain Bird Species - Barras, Arnaud G.; Blache, Sébastien; Schaub, Michael; Arlettaz, Raphaël (Frontiers in Ecology and Evolution, 2021)
Species- and population-specific responses to their environment may depend to a large extent on the spatial variation in life-history traits and in demographic processes of local population dynamics. Yet, those parameters and their variability remain largely unknown for many cold-adapted species, which are exposed to particularly rapid rates of environmental change. Here, we compared the demographic traits and dynamics for an emblematic bird species of European mountain ecosystems, the ring ouzel (Turdus torquatus). Using integrated population models fitted in a Bayesian framework, we estimated the survival probability, productivity and immigration of two populations from the Western European Alps, in France (over 11 years) and Switzerland (over 6 years). Juvenile apparent survival was lower and immigration rate higher in the Swiss compared to the French population, with the temporal variation in population growth rate driven by different demographic processes. Yet, when compared to populations in the northwestern part of the range, in Scotland, these two Alpine populations both showed a much lower productivity and higher adult survival, indicating a slower life-history strategy. Our results suggest that demographic characteristics can substantially vary across the discontinuous range of this passerine species, essentially due to contrasted, possibly locally evolved life-history strategies. This study therefore raises the question of whether flexibility in life-history traits is widespread among boreo-alpine species and if it might provide adaptive potential for coping with current environmental change.